Influence of bisphenol A and its analog bisphenol S on cocaine- and amphetamine-regulated transcript peptide–positive enteric neurons in the mouse gastrointestinal tract - Makowska, Krystyna; Fagundes, Kainã R. C.; Gonkowski, Sławomir (Frontiers in Molecular Neuroscience, 2023)
Bisphenol A (BPA) is used in large quantities for the production of plastics and is present in various everyday objects. It penetrates living organisms and shows multidirectional adverse influence on many internal organs. For this reason, BPA is often replaced in plastic production by other substances. One of them is bisphenol S (BPS), whose effects on the enteric nervous system (ENS) have not been explained. Therefore, the present study compares the influence of BPA and BPS on the number of enteric neurons immunoreactive to cocaineand amphetamine-regulated transcript (CART) peptide located in the ENS of the stomach, jejunum and colon. The obtained results have shown that both bisphenols studied induced an increase in the number of CART-positive enteric neurons, and the severity of changes depended on the type of enteric ganglion, the dose of bisphenols and the segment of the digestive tract. The most visible changes were noted in the myenteric ganglia in the colon.Moreover, in the colon, the changes submitted by BPS are more noticeable than those observed after BPA administration. In the stomach and jejunum, bisphenol-induced changes were less visible, and changes caused by BPS were similar or less pronounced than those 2 noted under the impact of BPA, depending on the segment of the gastrointestinal tract and ganglion type studied. The results show that BPS affects the enteric neurons containing CART in a similar way to BPA, and the BPS impact is even stronger in the colon. Therefore, BPS is not neutral for the gastrointestinal tract and ENS.